Exhaust emissions evaluation of Colombian commercial diesel fuels - Torres, Jaime; Bello, Arcesio; Sarmiento, Jose; Rostkowski, Jacek; Brady, Jeremy (CT&F - Ciencia, Tecnología y Futuro, 2003)
Ecopetrol, based on the results obtained in the study "The Effect of Diesel Properties on the Emissions of Particulate Matter" (Bello et al., 2000), reformulated the diesel fuel distributed in Bogotá, becoming it lighter and with a lower sulfur content. In order to evaluate the environmental benefits that the reformulation of diesel fuel generate in Bogotá, Instituto Colombiano del Petróledo (ICP), with the assistance of Emissions Research and Measurement Division (ERMD) from Environment Canada, arranged a research project to determine the changes in CO, THC, NOx, CO2 and Particulate Matter emissions. The research program was developed in two steps. First one, developed in Bogotá, involved a fleet test with 15 public service buses that normally operate in Bogota’s Savannah, using a portable emissions sampling technology developed for ERMD (DOES2) and following a representative transient driving cycle. Second step, carried out in ERMD’s Heavy-Duty Engine Emissions Laboratory in Ottawa, tested a 1995 caterpillar 3406E 324,5 kW (435 HP) diesel truck engine on the same samples of Colombian diesel fuels used in the fleet tests performed in Bogotá, baselining the tests with a Canadian Commercial Low Sulfur Diesel Fuel. The two commercial Colombian diesel fuels used had the following properties: High Sulfur Diesel (HSD), with 3000 ppm (0,3 wt%) of sulfur and a Final Boiling Point (FBP) of 633 K and the new reformulated diesel fuel, with 1000 ppm (0,1 wt%) of sulfur and FBP of 613 K, which is currently been distributed in Bogotá. Fleet test show small reduction on CO, THC and TPM, and small increments on CO2 and NOx, but with not statistically significant results, while engine testing shows an strong reduction of 40,8% in TPM when you use the new reformulated diesel fuel (0,1wt% of sulfur) instead of high sulfur diesel.